2006
DOI: 10.1111/j.1349-7006.2006.00221.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetically engineered Bifidobacterium longum for tumor‐targeting enzyme‐prodrug therapy of autochthonous mammary tumors in rats

Abstract: A fundamental obstacle in systemic therapy for cancer patients is the specific targeting of therapy directly to solid tumors. A strain of the domestic bacterium Bifidobacterium longum, which is non-pathogenic and anaerobic, showed selective localization to and proliferation within solid tumors after systemic application. Here, we propose a novel approach to cancer gene therapy in which anaerobic and non-pathogenic bacteria of the genus B. longum are used to achieve tumor-specific gene delivery and enzymeprodru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
65
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(67 citation statements)
references
References 31 publications
2
65
0
Order By: Relevance
“…In addition, E. coli Nissle 1917-as an E. coli strain-has a comparatively simple genetic basis and therefore can be modified into an effective drug-producing machine more easily than other bacteria. In bacteriolytic cancer therapy, most studies focus on the use of cytokines (18,36), prodrugs (6,24), or bacteria per se (4, 43) for inhibiting tumor growth or metastasis. Here, we used the bacteria to express a secretory antitumor protein for cancer therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, E. coli Nissle 1917-as an E. coli strain-has a comparatively simple genetic basis and therefore can be modified into an effective drug-producing machine more easily than other bacteria. In bacteriolytic cancer therapy, most studies focus on the use of cytokines (18,36), prodrugs (6,24), or bacteria per se (4, 43) for inhibiting tumor growth or metastasis. Here, we used the bacteria to express a secretory antitumor protein for cancer therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies clearly showed that some bacteria can target and proliferate in solid tumors, significantly inhibiting the growth of tumors (32,34). So far, bacteria such as Clostridium (1,4,8), Salmonella (3,19,21), Bifidobacterium (24,41) and Escherichia coli (6,27) have been clinically employed for the delivery of drugs, RNA (35,42), and immune factors (18,36). Also, these bacteria are often used in combination with traditional methods such as radiation (4) and chemotherapy (25) for cancer therapy.…”
mentioning
confidence: 99%
“…107 B. longum selectively produces CD in hypoxic mammary tumor tissues in rats, and converts 5-FC into 5-FU in vivo. [108][109][110] This system could be significantly improved by combination with MR imaging technology.…”
Section: Combined Imaging and Therapymentioning
confidence: 99%
“…2,4 Both Clostridia and Bifidobacteria have been successfully used for 'enzyme-prodrug' therapy. 41 Owing to their obligate anaerobic nature, ability to form spores and ease of transformation, Clostridia are especially suited to AGT for tumors. 42,43 Further, their ability to colonize tumors in vivo can be enhanced by deletion of genes associated with basal oxygen tolerance, such as that encoding superoxide dismutase.…”
Section: Alternative Gene Therapymentioning
confidence: 99%